Magnetic Resonance Imaging for Patellofemoral Chondromalacia: Is There a Role for T2 Mapping?. Issue 11 (16th November 2017) - van Eck, Carola F.; Kingston, R. Scott; Crues, John V.; Kharrazi, F. Daniel
Background: Patellofemoral pain is common, and treatment is guided by the presence and grade of chondromalacia. Purpose: To evaluate and compare the sensitivity and specificity in detecting and grading chondral abnormalities of the patella between proton density fat suppression (PDFS) and T2 mapping magnetic resonance imaging (MRI). Study Design: Cohort study; Level of evidence, 2. Methods: A total of 25 patients who underwent MRI of the knee with both a PDFS sequence and T2 mapping and subsequently underwent arthroscopic knee surgery were included. The cartilage surface of the patella was graded on both MRI sequences by 2 independent, blinded radiologists. Cartilage was then graded during arthroscopic surgery by a sports medicine fellowship–trained orthopaedic surgeon. Reliability, sensitivity, specificity, and accuracy were determined for both MRI methods. The findings during arthroscopic surgery were considered the gold standard. Results: Intraobserver and interobserver agreement for both PDFS (98.5% and 89.4%, respectively) and T2 mapping (99.4% and 91.3%, respectively) MRI were excellent. For T2 mapping, the sensitivity (61%) and specificity (64%) were comparable, whereas for PDFS there was a lower sensitivity (37%) but higher specificity (81%) in identifying cartilage abnormalities. This resulted in a similar accuracy for PDFS (59%) and T2 mapping (62%). Conclusion: Both PDFS and T2 mapping MRI were reliable but only moderately accurate in predicting patellar chondromalacia found during knee arthroscopic surgery.